How to romance a rake eaudiobook - Collins, Manda (Ugly Ducklings, 2012)
What's a nice girl like Miss Juliet Shelby doing at a place like Lord Deveril's ballroom? With her shy demeanor, she's a total stranger to the dance floor and a source of mockery for the ton. So imagine her surprise when Deveril gallantly comes to her defense—and offers to teach her to dance! Juliet can hardly believe the most handsome bachelor in London would notice her, until he takes her in his arms and sets her heart ablaze. Lord Alec Deveril has never felt such a spark of attraction for an unmarried lady before. Unlike the "fashionable" ladies he's accustomed to, Juliet possesses a generous spirit, a fiery intelligence—and an explosive secret. Deep in the London underworld, a dear friend has vanished, and Juliet fears the worst. Deveril insists on helping, escorting her through the darkest alleys in town. But he too is hiding a shocking secret—and the only way he can defeat the devil in his past is to seduce the angel in his arms . . .